2021
DOI: 10.1186/s12978-021-01115-w
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of perinatal outcomes and birth defects amongst adolescent and older Ugandan mothers: evidence from a hospital-based surveillance database

Abstract: Background Uganda has one of the highest adolescent pregnancy rates in sub-Saharan Africa. We compared the risk of adverse birth outcomes between adolescents (age 12–19 years) and mothers (age 20–34 years) in four urban hospitals. Methods Maternal demographics, HIV status, and birth outcomes of all live births, stillbirths, and spontaneous abortions delivered from August 2015 to December 2018 were extracted from a hospital-based birth defects surve… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Our overall finding of HR 1.8 for hazard of mortality among neonates born to adolescent mothers is comparable to findings of a nationwide study conducted in Nigeria, a similar setting, by Akinyemi et al that found hazard ratios of 1.75 and 1.5 for its 2008 analytical models, comparing neonatal deaths among adolescent mothers to mothers 20–35 years old [ 52 ]. Other studies across the globe have reported comparable higher risks of neonatal death among neonates born to adolescent mothers [ 5 , 19 , 20 , 53 , 54 ]. Furthermore, the USA 2020 national report indicated highest NMR among adolescent mothers compared to older mothers [ 55 ].…”
Section: Discussionmentioning
confidence: 89%
“…Our overall finding of HR 1.8 for hazard of mortality among neonates born to adolescent mothers is comparable to findings of a nationwide study conducted in Nigeria, a similar setting, by Akinyemi et al that found hazard ratios of 1.75 and 1.5 for its 2008 analytical models, comparing neonatal deaths among adolescent mothers to mothers 20–35 years old [ 52 ]. Other studies across the globe have reported comparable higher risks of neonatal death among neonates born to adolescent mothers [ 5 , 19 , 20 , 53 , 54 ]. Furthermore, the USA 2020 national report indicated highest NMR among adolescent mothers compared to older mothers [ 55 ].…”
Section: Discussionmentioning
confidence: 89%
“…As per a study conducted in Missouri, the risk of intrapartum stillbirth is four times and 50% higher in older adolescent pregnant females than in adult pregnant women [50]. In a cross-sectional study conducted in Hebei, China, by Zhang et al worked over four years (2013-2017) with 238,593 women subdivided into the adolescent group (10)(11)(12)(13)(14)(15)(16)(17)(18)(19) and adult group (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34), adolescent women had a higher risk of stillbirth and neonatal death as compared to the adult group. It was also noted that preterm deliveries were at a higher rate in the adolescent group [51].…”
Section: Adolescent Pregnancy and Stillbirthsmentioning
confidence: 99%
“…Patients aged 10-19 years have a higher risk to develop preeclampsia, eclampsia, and systemic infections [9,11]. Newborns from young mothers are also exposed to increased risks for low birth weight, prematurity, stillbirth, congenital anomalies, and early neonatal demise [9,11,[12][13][14][15][16]. The explication of these complications may result in the lack of maturation of biological, psychological, and sociological systems [12,16].…”
Section: Introductionmentioning
confidence: 99%